Commercial Claims–Based Comparison of Survival and Toxic Effects of Definitive Radiotherapy vs Primary Surgery in Patients With Oropharyngeal Squamous Cell Carcinoma - Sher, David J. (JAMA Otolaryngol Head Neck Surg, 2018)
IMPORTANCE: Definitive radiotherapy (RT) and primary surgery (PS) are considered to be equally viable local therapy modalities for oropharyngeal squamous cell carcinoma (OPSCC). The comparative effectiveness of these therapies is often debated, and treatment decisions are based on a paucity of comparative data. OBJECTIVE: To examine the differences in overall survival and key toxic effects in patients with OPSCC treated with RT and PS. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort analysis used the HealthCore Integrated Research Database to identify 884 patients diagnosed with OPSCC from January 1, 2007, to December 31, 2014. Patients were categorized as receiving definitive RT (with or without chemotherapy) or PS (with or without adjuvant RT or chemoradiotherapy). Administrative claims data were linked with state cancer registries from California, Connecticut, Georgia, Kentucky, New York, and Ohio. Data analysis was performed from February 29, 2016, to February 6, 2018. EXPOSURES: Definitive RT or PS. MAIN OUTCOMES AND MEASURES: Overall survival was analyzed using Cox proportional hazards regression. Risks of gastrostomy dependence, esophageal stricture, and osteoradionecrosis were determined through claims and analyzed using logistic regression. RESULTS: A total of 884 patients (608 [68.8%] in the RT group and 276 [31.2%] in the PS group; mean [SD] age, 61.5 [10.7] years; 727 [82.2%] male; 842 [95.3%] white) were included in this study. The 3-year overall survival was 76% among patients treated with RT and 81% among patients treated with PS (hazard ratio, 0.76; 95% CI, 0.54-1.01). On multivariable analysis, increasing age, female sex, and low income were associated with inferior survival; treatment type was not. Patients treated with RT were more likely to have gastrostomy dependence within the first year (391 [64.3%] vs 127 [46.0%]; adjusted OR, 0.57; 95% CI, 0.42-0.77). After treating chemotherapy as an effect modifier, there was no difference between modalities. Treatment type was not associated with esophageal stricture or osteoradionecrosis risk. Mean costs were approximately $100 000 for payers and $5000 for patients, with no adjusted differences between RT and PS. CONCLUSIONS AND RELEVANCE: This study suggests that RT and PS are equally viable treatment options for OPSCC; therefore, local therapy decisions may be individualized to each patient. However, the frequent addition of chemotherapy was associated with increased gastrostomy dependence among patients undergoing RT, which may be relevant in clinical decision making.